Validity and Reliability of the Pittsburgh Sleep Quality Index Bahasa Indonesian Version among Type 2 Diabetes Mellitus Patients - Dita Hanna Febriani; Anunsia Prastiwi (PT.Mantaya Idea Batara, 2026)
ackground: Poor sleep quality is a prevalent symptom reported by type 2 diabetes mellitus patients, and with impaired glycemic control, decreased quality of life, psychological distress, and an increased risk of diabetes-related complications. Sleep disturbances may also negatively affect treatment adherence and daily functioning. Despite its clinical significance, a culturally adapted and validated instrument for assessing sleep quality in Indonesian patients with type 2 diabetes mellitus remains limited. To address the existing literature gap, this study translated and adapted the Pittsburgh Sleep Quality Index (PSQI) for patients with type 2 diabetes mellitus in Indonesia and evaluated its validity and reliability. Methods: This study employed a quantitative descriptive design using a cross-sectional approach. The translation and cultural adaptation process followed recommended guidelines, including translation, expert panel review, and pilot testing. Content validity was assessed by a panel of experts. Reliability testing was conducted using Cronbach’s alpha to assess internal consistency. A convenience sample of 140 adult patients with type 2 diabetes mellitus completed the instrument. Results: The item content validity and a Cronbach’s alpha coefficient were 1 and 0.712, respectively. The findings demonstrated that the Indonesian version of the PSQI-I had satisfactory validity and reliability. The content validity index indicated good relevance. The overall Cronbach’s alpha indicates acceptable internal consistency reliability. Conclusion: Bahasa Indonesia version of the PSQI (PSQI-I) is a valid and reliable instrument for assessing sleep quality among Indonesian patients with type 2 diabetes mellitus. This instrument may be used in clinical and nursing practice, as well as in future research, to evaluate sleep-related problems in this population.